Environmental, Social and Governance Disclosure Impacts on Earnings Management in Indonesia - Itan, Iskandar; Nazara, Eka Prasetya; Karjantoro, Handoko (Global Financial Accounting Journal, 2025)
Purpose - This study aims to analyze the impact of Environmental, Social, and Governance (ESG) disclosure on earnings management practices among companies listed on the Indonesia Stock Exchange (IDX). It explores how ESG transparency influences corporate financial reporting behavior. Research Method - This study uses data from Thomson Reuters, covering 86 IDX-listed companies that disclosed ESG information during the 2019-2023 period. Findings - It revealed that ESG disclosure in the environmental and social dimensions is found to reduce earnings management practices, while governance disclosure shows no significant effect. Companies with higher revenue levels are more effective in leveraging ESG disclosure to enhance transparency. Implication - This study offers a novel contribution by examining the influence of ESG disclosure on earnings management in Indonesia, while also considering company revenue levels as a comparative factor. The findings hold important policy and practical implications, especially for regulators and corporate management, in understanding the broader impact of ESG practices on the integrity of financial reporting.